Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.joca.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

T1ρ and T2 relaxation times predict progression of knee osteoarthritis

Abstract: SUMMARY Objective To evaluate whether T2 and T1ρ relaxation times of knee cartilage determined with 3T magnetic resonance imaging (MRI) at baseline predict longitudinal progression of cartilage degenerative changes. Methods Quantitative analysis of cartilage was performed using 3T MRI with both T2 and T1ρ mapping techniques in 55 subjects without evidence of severe osteoarthritis (OA) [Kellgren–Lawrence (KL) score of 0–3] at baseline. Morphological abnormalities of cartilage, menisci, ligaments and bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 36 publications
8
109
1
Order By: Relevance
“…This is important considering the fact that interventions to prevent the onset of OA are likely to be more effective before radiographic changes have occurred. Furthermore, it has been shown that MR relaxation measures of cartilage predict future progression of OA [36,43]. Wise et al [54] also reported that women have greater prevalence of valgus alignment, which was also seen in our cohorts.…”
Section: Discussionsupporting
confidence: 69%
“…This is important considering the fact that interventions to prevent the onset of OA are likely to be more effective before radiographic changes have occurred. Furthermore, it has been shown that MR relaxation measures of cartilage predict future progression of OA [36,43]. Wise et al [54] also reported that women have greater prevalence of valgus alignment, which was also seen in our cohorts.…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, to our knowledge, the effect of weight loss on the morphologic degeneration of knee joint tissues has not been assessed. MR imaging is the most sensitive modality with which to depict subtle morphologic abnormalities, and it can reveal early structural osteoarthritic findings, including cartilage and meniscus defects (22)(23)(24).…”
Section: Database and Participantsmentioning
confidence: 99%
“…Additionally, T 1ρ quantification has been used in the attempt to stratify subjects at risk of developing post-traumatic osteoarthritis (PTOA) following anterior cruciate ligament (ACL) injury and reconstruction (11,12). Prolongation of T 1ρ relaxation times has been reported in OA subjects, specifically in the medial compartment (13,14). In contrast, in subjects with ACL injury, elevation in T 1ρ is observed in the posterior lateral tibia immediately after injury, the characteristic site of the pivot shift contusion (15).…”
Section: Introductionmentioning
confidence: 99%